Think pair share as an effort to foster students' literacy awareness and individual accountability character - Jannah, Nita Maghfiratul; Fitriani, Fitriani; Herbyanti, Neneng; Indrawan, Adam; Pratiwi, Dwiyani; Jamilah, Jamilah; Handayani, Sri (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2023)
Cooperative learning is the use of small groups for education in which students collaborate to optimize their own and each other's learning. Cooperative learning has been used to solve many problems both cognitive and social inability. There are many obstacles that may occur in the process of students learning to work together, including a lack of literacy awareness and individual accountability. This study was aimed at improving students' literacy awareness and individual accountability and at the same time improving s English writing ability. This action research was carried out in one of junior high school in Yogyakarta in English subject particularly using recount text material. The sample was chosen using random sampling technique. There were 31 students participated in this study. The data were gathered using interview, survey, test and documentation. The data gained then were analyzed both qualitatively and quantitatively. The findings show that Think Pair Share is significantly improve students' cognitive ability, the English writing ability. However, the results of the t-test analysis did not reflect a significant increase in student literacy awareness and individual accountability. The increase occurred in the atmosphere of the learning process where there was a reduction in students with smartphone dependency in learning outside of learning interests and the tendency of students to try to find online learning resources through electronic dictionaries, unfortunately this impact was not significant enough to be seen significantly from quantitative data.